Clinical profile and outcome of poisoning in children admitted to a tertiary referral center in South India - Vasanthan, Mullai; James, Saji; Shuba, S; Abhinayaa, J; Sivaprakasam, Elayaraja (Indian Journal of Child Health, 2015)
Background: Childhood poisoning covers the entire gamut from accidental ingestion in toddlers and preschool children to intentional overdosage in adolescents. The poisons range from fuel to drugs and other chemicals. Objective: To determine the epidemiology, clinical profile, and outcome of children presenting with acute poisoning in a tertiary care center in south India. Materials and Methods: All patients from the age of 1 month to 18 years, admitted during the 1-year study period with a history of poisoning, were included. Animalbites, snake, and scorpion envenomation were excluded. The data were analyzed using SPSS software, version 16. A multivariate analysis was also done and a p